Utilization of Library Technology Services for Academic Performance of Senior Secondary School Students in Zaria Local Government Area, Kaduna State - Dada, Kayode Sunday John (Athallah Publishing, 2025)
This study investigates the availability and challenges of library technology services for senior secondary school students in Zaria Local Government Education Authority (LGEA), Kaduna State, Nigeria, using a descriptive survey design. Data were collected from 364 students across 12 public secondary schools via a validated questionnaire (LTSAUCQ) with a 91% response rate. Findings reveal that Digital Information Resources (e.g., online catalogs, e-books) are relatively available (81.8%, mean = 0.818), followed by Library Management Systems (60.2%, mean = 0.602), while Specialized Technology Services (e.g., AI, digital repositories) are least available (41.8%, mean = 0.418), with an overall availability of 61.2%. However, significant utilization challenges persist, with Training and Skills Challenges being most prevalent (77.5%, mean = 0.775), followed by Infrastructure and Resource Challenges (70.1%, mean = 0.701) and Access and Usability Challenges (63.4%, mean = 0.634). The overall challenge prevalence (70.3%) exceeds service availability, indicating a critical implementation gap. This misalignment highlights that mere technology provision without addressing training, infrastructure, and usability barriers results in suboptimal educational outcomes. The low availability of advanced technologies risks widening the digital divide, limiting students’ readiness for technology-intensive environments. The study highlight the need for holistic interventions, including infrastructure upgrades, comprehensive training, and user education programs, to enhance library technology utilization and support academic performance. These findings advocate for policy reforms prioritizing school library development to foster digital literacy and equitable educational opportunities.